Oxaprozin-Induced Apoptosis on CD40 Ligand-Treated Human Primary Monocytes Is Associated with the Modulation of Defined Intracellular Pathways. (10th August 2009) - Montecucco, Fabrizio; Bertolotto, Maria; Ottonello, Luciano; Quercioli, Alessandra; Mach, François; Dallegri, Franco
Abstract : The modulation of CD40L activity might represent a promising therapeutic target to reduce monocyte inflammatory functions in chronic diseases, such as rheumatoid arthritis. In the present study, we investigated the possible influence of nonsteroidal anti-inflammatory drugs (NSAIDs) on CD40L-induced monocyte survival. Monocytes were isolated from buffy coats by using Ficoll-Percoll gradients. Monocyte apoptosis was evaluated by fluorescence microscopy on cytopreps stained with acridine orange or using flow cytometry analysis of Annexin-V and Propidium Iodide staining. Akt and NF-κ B activation was assessed using western blot. Caspase 3 activity was determined spectrophotometrically. Among different NSAIDs, only oxaprozin dose-dependently increased apoptosis of CD40L-treated monocytes. Oxaprozin pro-apoptotic activity was associated with the inhibition of CD40L-triggered Akt and NF-κ B phosphorylation and the activation of caspase 3. In conclusion, our data suggest that oxaprozin-induced apoptosis in CD40L-treated human monocytes is associated with previously unknown cyclooxygenase (COX)-independent pathways. These intracellular proteins might be promising pharmacological targets to increase apoptosis in CD40L-treated monocytes.